The Role of the Family in Encouraging School Age Children's Interest in Reading at SDN Sosak Praya Timur - Saharudin, Saharudin (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2026)
This study aims to describe the role of families in encouraging reading interest among school-age children at SDN Sosak Elementary School in Praya Timur District, Central Lombok. The background of this study is based on the low reading interest among children in elementary school environments, which requires active support from families as the first and primary educational environment. This study uses a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation of parents, teachers, and students. The results of the study show that families play an important role in building children's interest in reading through various forms of action, including the habit of reading at home, parental role modeling, providing motivation, providing reading materials, and accompanying children while reading. Factors that influence interest in include family support, socioeconomic conditions, availability of reading materials, and the role of the school. Despite limited facilities, families demonstrate a strong commitment to building a culture of literacy through simple but consistent means.